Differences in the physical components of speed, agility, and muscle endurance based on playing position in Indonesian amateur women soccer athletes - Arfiansyah, Eggy Nur (Universitas Tanjungpura, 2024)
Scientific interest in women's soccer has increased over the past few years. There are several factors that can affect the performance of female soccer athletes, including the composition that supports running performance (speed, agility, and muscular endurance). This is to identify players who may be considered important for the successful execution of tactical roles and reference norms for developing future soccer playing talent. The purpose of this study was to identify differences in speed, agility, and muscular endurance based on playing position in amateur female athletes. The population and sample in this study were 24 amateur female soccer players. This research method uses an analytical approach with data description. Furthermore, it was analyzed using SPSS software version 26. The results showed significant differences between the variables tested according to the player's position in the team could not be determined with the significance results for the speed variable of 0.001 0.05, then for the agility value of 0.001 0.05, and for the muscle endurance variable of 0.000 0.05. The conclusion of this study is that there are significant differences in speed, agility, and muscle endurance in amateur female soccer players based on playing position. However, players must maintain and improve their level of physical fitness to support tactical performance during matches or seasons.